Features of clinical course and skin lesions associated with new coronavirus infection in children - I. A. Plotnikova; V. L. Zelentsova; I. G. Lavrik; A. A. Egorov; S. A. Nakhratova (Аллергология и Иммунология в Педиатрии, 2023)
This article discusses the features of skin lesions and the clinical course of a new coronavirus infection in children. Among the extrapulmonary signs associated with COVID-19, dermatologic manifestations have increasingly appeared in the past few months.   The aim of the study was to correlate available data in the literature on variants of dermatological manifestations of COVID-19 in children with clinical examples of skin lesions associated with this infection in patients seen by a specialized dermatologist.   We used PubMed and Cyberleninka search engines for the period 2020–2021 Systematized variants of dermatological syndromes in children who had undergone COVID-19 described in reviews of materials by domestic and foreign researchers. The authors analyzed the primary medical records and photographic archives of children admitted to the outpatient clinic of a dermatologist at Yekaterinburg municipal clinical hospital No. 9 for 1 month after the established family contact with a new case of coronavirus infection. Analysis of scientific literature data showed that SARS-CoV-2 virus-associated skin lesions in children were more frequent in the mild course of infection, presumably with the implementation of an immunocomplex mechanism of vascular and epithelial damage. The pronounced vascular damage is a distinctive feature of COVID-19-related exanthemas, especially when localized on the fingers of the lower extremities. This article presents 5 clinical cases of children with various forms of acute dermatoses: urticaria, frostbite-like exanthema of the fingers, onychodystrophy, alopecia, and generalized pustular psoriasis of Zumbush. Only three children had laboratory confirmation of SARS-CoV-2 infection.